THE EFFECT OF THE IMPLEMENTATION OF GREEN ACCOUNTING AND MATERIAL FLOW COST ACCOUNTING ON PROFITABILITY (A STUDY ON MINING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE) - selenita, selenita; indrayani; Sahara, Ira (Islamic Financial And Accounting Review, 2025)
Green accounting and material flow cost accounting are approaches in accounting that are a manifestation of the company's concern in managing environmental impacts in its operational activities. This study aims to determine the effect of the implementation of green accounting and material flow cost accounting on profitability in mining companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The research method used is quantitative with an associative approach. This study takes a sample of companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period using secondary data obtained through the annual report and sustainability report for the 2019-2023 period and the data is tested using descriptive statistical analysis, classical assumption test in the form of normality test, multicollinearity test, autocorrelation test and heteroscedasticity test, regression analysis test linear and hypothesis tests in the form of determination coefficient test (Adjust R2), t test and F test. The results obtained from this study are normally distributed data. Partially, green accounting has a significant effect on the company's profitability. Meanwhile, material flow cost accounting partially does not show a significant influence on profitability. Simultaneously, green accounting and material flow cost accounting together affect the company's profitability. The determination coefficient test showed that some of the variation in profitability could be explained by the two independent variables, while the rest was influenced by other variables. These results reinforce the importance of the comprehensive application of environmental accounting practices in the planning and management of the company's operational activities, especially in the mining industry sector that has a major impact on the environment.